The effective shear modulus for ann-layered composite sphere - Lenz, Peter; Dammann, Christian; Mahnken, Rolf (PAMM)

Possibilistic and stochastic analysis using for rubber‐like materials - Penner, Eduard; Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

A multivariate stochastic material model with correlated material parameters - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Variational integrators of higher order for constrained dynamical systems - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

C1-continuous time integration based on cubic Hermite interpolation - Mergel, J.C.; Sauer, R.A.; Ober-Blöbaum, Sina (PAMM)

Time transformed mixed integer optimal control problems with impacts - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

Higher order variational integrators in optimal control theory - Ober-Blöbaum, Sina (PAMM)

Variational multirate integration in multi-body dynamics - Gail, T.; Leyendecker, S.; Ober-Blöbaum, S. (PAMM)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
In this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

Multiobjective Optimization of the Flow Around a Cylinder Using Model Order Reduction - Peitz, Sebastian; Dellnitz, Michael (PAMM)
n this article an efficient numerical method to solve multiobjective optimization problems for fluid flow governed by the Navier Stokes equations is presented. In order to decrease the computational effort, a reduced order model is introduced using Proper Orthogonal Decomposition and a corresponding Galerkin Projection. A global, derivative free multiobjective optimization algorithm is applied to compute the Pareto set (i.e. the set of optimal compromises) for the concurrent objectives minimization of flow field fluctuations and control cost. The method is illustrated for a 2D flow around a cylinder at Re = 100.

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, Kathrin (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, Maik; Ober-Blöbaum, Sina; Leyendecker, Sigrid (PAMM)

Relaxing mixed integer optimal control problems using a time transformation - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (Proceedings of Applied Mathematics and Mechanics)

Multiobjective optimal control of fluid mixing - Ober-Blöbaum, Sina; Padberg-Gehle, K. (PAMM)

Adaptive FEM with goal-oriented error estimation and an approximation of the dual problem for inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Uncertainty quantification for linear elastic bodies with two fluctuating input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

A coupled phase-field - Cahn-Hilliard model for lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Transition from hyperelastic micromorphic to micropolar and microstrain continua - Leismann, Thorben; Mahnken, Rolf (PAMM)

Non-linear Stochastic Finite Element - Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

Optimal Parameter Tuning for Multiclass Support Vector Machines in Machinery Health State Estimation - Kimotho, James Kuria; Sextro, Walter (PAMM)
The increasing demand for high reliability, safety and availability of technical systems calls for innovative maintenance strategies. The use of prognostic health management (PHM) approach where maintenance action is taken based on current and future health state of a component or system is rapidly gaining popularity in the maintenance industry. Multiclass support vector machines (MC-SVM) has been identified as a promising algorithm in PHM applications due to its high classification accuracy. However, it requires parameter tuning for each application, with the objective of minimizing the classification error. This is a single objective optimization problem which requires the use of optimization algorithms that are capable of exhaustively searching for the global optimum parameters. This work proposes the use of hybrid differential evolution (DE) and particle swarm optimization (PSO) in optimally tuning the MC-SVM parameters. DE identifies the search limit of the parameters while PSO finds the global optimum within the search limit. The feasibility of the approach is verified using bearing run-to-failure data and the results show that the proposed method significantly increases health state classification accuracy.

Tire footprint analysis depending on the elastokinematics of a multi-link suspension system using multi-body dynamics simulation - Kohl, Sergej; Sextro, Walter; Zuber, Armin (PAMM)
An automotive suspension system represents one of the most complex and important systems in a passenger vehicle, which has to ensure a robust and optimized contact between the wheels and the road at any time. For improving a suspension system it is important to take an investigative look at the interaction between suspension, tire and road dynamics. Thus a part of a study into aspects of suspension modeling on multi-body simulations of rear multi-link suspension system dynamics with focus on the tire footprint area is presented in this work.

Contact Modeling in Multibody Systems with Elastic Bodies in High-Frequency Applications - Schulze, Sebastian; Sextro, Walter; Grüter, Frank (PAMM)
This paper discusses the refinement of multibody models by integration of flexible bodies and by considering nonlinearities from contacts. It presents common approaches for contact modeling in multibody simulations and strategies to include flexible bodies. A contact model is implemented in the elastic multibody model. Experimental results show that significant effects of system dynamics can be modeled by use of a multibody model including elastic bodies and contacts.

Approximation of the dual problem for error estimation in inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Macroscopic and mesoscopic modeling based on the concept of generalized stresses for cutting simulation - Cheng, Chun; Mahnken, Rolf; Uhlmann, Eckart; Ivanov, Ivan Mitkov (PAMM)

A macroscopic consitutive model on induced anisotropy for polymers with weighting functions - Dammann, Christian; Mahnken, Rolf (PAMM)

Parameter identification for rubber materials with artificial higher dimensional data - Mahnken, Rolf; Nörenberg, Nicole (PAMM)

Bainitic variant evolution in a low-alloyed steel including numerical aspects - Ehlenbröker, Ulrich; Mahnken, Rolf (PAMM)

Asynchronous variational Lie group integration for geometrically exact beam dynamics - Demoures, Francois; Gay-Balmaz, Francois; Leitz, Thomas; Leyendecker, Sigrid; Ober-Blöbaum, Sina; Ratiu, Tudor S. (PAMM)

Optimization for discretized switched systems - Flaßkamp, Kathrin; Murphey, Todd; Ober-Blöbaum, Sina (PAMM)

Computing time investigations for variational multirate integration - Gail, Tobias; Leyendecker, Sigrid; Ober-Blöbaum, Sina (PAMM)

A Multi-Mechanism Model for Cutting Simulations Combining Visco-plastic Asymmetry and Phase Transformation - Cheng, Chun; Mahnken, Rolf; Uhlmann, Eckart; Ivanov, Ivan Mitkov (PAMM)

Optimal Control on Stable Manifolds for a Double Pendulum - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Dellnitz, Michael; Trächtler, Ansgar (PAMM)

Carbon Fibre Prepregs: Simulation of a Thermo-Mechanical-Chemical Coupled Problem - Hankeln, Frederik; Mahnken, Rolf (PAMM)

Adaptive FEM with Stabilized Elements for Parameter Identification of Incompressible Hyperelastic Materials - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

A stochastic model for the direct and inverse problem of adhesive materials - Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Micromechanical modeling of bainitic phase transformation - Schneidt, Andreas; Antretter, Thomas; Mahnken, Rolf (PAMM)

Modeling of induced anisotropy at large deformations for polymers - Caylak, Ismail; Mahnken, Rolf (PAMM)

Simulation of Deep Drawing of Carbon Fibre Prepregs - Hankeln, Frederik; Mahnken, Rolf (PAMM)

Meso-Macro Modelling of Coated Forming Tools under Thermal Shock Conditions - Sauerland, Kim-Henning; Mahnken, Rolf (PAMM)

An error indicator for parameter identification with stabilized mixed tetrahedrals - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Stabilized mixed triangular finite elements at large deformations using area bubble functions - Caylak, Ismail; Mahnken, Rolf; Widany, Kai-Uwe (PAMM)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Reibungsdämpfung in ausgedehnten, verschraubten Fügestellen - Hölzl, Johannes Sebastian; Sextro, Walter (PAMM)
Bei der Konstruktion von Maschinen ist es oftmals erforderlich, Schwingungen minimal zu halten. Um z.B. die Lebensdauer zu erhöhen, Material einzusparen oder den Geräuschpegel gering zu halten muss oft ein großer Aufwand zur Dämpfung von auftretenden Schwingungen betrieben werden. In vielen technischen Anwendungen werden Einzelteile miteinander verschraubt. Diese Fügestellen können gezielt und mit wenig Aufwand zur Schwingungsdämpfung herangezogen werden. Die Berechnung des dynamischen Verhaltens verschraubter Strukturen stellt immer noch eine Herausforderung dar. Es wurde eine Methode entwickelt, um den eingeschwungenen Zustand elastischer, miteinander verschraubter Körper mit rauen Fügestellen bei periodischer Anregung zu berechnen. Als Basis dienen Finite Elemente Modelle der einzelnen Teile, deren Freiheitsgrade durch modale Kondensation reduziert werden. Unter Anwendung des Verfahrens von Ritz und Galerkin wird eine Näherungslösung für den eingeschwungenen Zustand des nichtlinearen, gekoppelten Systems ermittelt. Abhängig von den Schraubenvorspannkräften sowie den bestimmenden Parametern der Kontaktflächen, Rautiefe und Reibungskoeffizient, kann die Systemantwort berechnet und optimiert werden. Um die Berechnungsmethode zu verifizieren wurden Experimente durchgeführt. Der Vergleich zwischen Messung und Rechnung zeigt eine gute Übereinstimmung. ({©} 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)